Educational inequalities and alcohol-related consequences in Brazil. - Oliveira, Leandro Machado; Demarco, Flávio Fernando; Zanatta, Fabrício Batistin (Alcohol & Alcoholism, 2024)
Aims This study aimed to test whether the alcohol harm paradox (AHP) is observed in Brazil by investigating (i) the association between educational attainment and alcohol-related consequences (ARC) and (ii) the contribution of average alcohol volume consumed (AVC), past-month heavy episodic drinking (HED), smoking, body mass index (BMI), and depression in accounting for the disparities in ARC. Methods We analysed data from the 2019 Brazilian National Health Survey, a nationally representative household survey. The composite ARC outcome was considered present when an individual reported a past-year episode of activity failure, amnesia, and concern by others due to alcohol consumption. Adjusted binary logistic regression models were fitted using a hierarchical approach to calculate the odds ratios (OR) and respective 95% confidence intervals (CI), and to assess the contribution of each set of variables in attenuating the educational differences in ARC. Results Those from the lowest educational strata (incomplete elementary school) exhibited higher odds of ARC than their counterparts (OR: 2.03; 95% CI: 1.73–2.37). Although smoking, BMI, and depression attenuated the educational gradient (i.e. reduced the difference between reference and riskier categories) in ARC by ~13%, the adjustment for AVC and HED amplified inequalities by 0.3% and 5.7%, respectively. Conclusion We found evidence of the AHP in Brazil. Educational inequalities in ARC were scarcely attenuated by behavioural factors, and a suppression effect was noted when adjusting for AVC and HED.